From the junior to the national swim team: A milestone - Mullen, J. (2016)
The shift from the junior to the national swimming team is one of the most challenging milestones in a swimmer's career. Indeed there are evidences that the ability to predict swimming performance increases sharply around such chronological ages (Costa et al., 2011). The 4th FINA World Junior Swimming Championships are being held at this moment in Dubai. A question crossed my mind: what did happen to the swimmers that participated in previous editions of this competition. They will be competing at top-level, attending to major championships a few years later or not? Let's consider an Olympic cycle. Since coaches have a long term view in what concerns to training design and periodization of talented and world-ranked swimmers, at least 3-4 seasons (i.e. an Olympic Cycle) (Costa et al., 2009) might be needed to have some clues. So, it was decided to do a retrospective analysis of what happened to the finalists of the 2nd FINA World Junior Swimming Championships (held in Monterrey, 2008). This analysis looked at which of these swimmers competed in the 2012 Olympic Games year and, the recent, 2013 World Championship, or both major competitions. The aim was to analyze and describe how many of the 2nd FINA World Junior Swimming Championships finalists also participated in the London 2012 Olympic Games and Barcelona 2013 World Championships, a little bit more than 4 years later (i.e., an Olympic cycle later). 2nd FINA World Junior Swimming Championships results were retrieved from the FINA website (www.fina.org).